Awareness and knowledge regarding maternal periodontal status and associated pregnancy outcomes among the gynecologists of Hubli-Dharwad - Shiphalika Sinha; Pragathi Raghavendra Bhat; Vivek Vijaykumar Govekar; Vijay Ashok Trasad; Anirudh Balakrishna Acharya (Wolters Kluwer Medknow Publications, 2020)
Introduction: Periodontitis is an inflammatory disease of gingiva and its supporting structures and is known to cause systemic infection which has adverse effect on pregnancy outcomes, such as preterm birth, preeclampsia, or miscarriage, which have been linked to maternal periodontitis. Aim: Thus, this study aimed to evaluate the knowledge and awareness regarding the association of periodontitis and adverse pregnancy outcomes among the gynecologists practicing in Hubli-Dharwad city. Materials and Methods: The study involved a survey for 50 practicing gynecologists in Hubli-Dharwad city, a pretested close-ended questionnaire was distributed comprising 10 questions on oral health for expectant mothers, and thus, their knowledge and awareness levels were assessed. Results: The results showed that majority of gynecologists agreed importance of maintaining good general health during pregnancy and supported that providing dental treatment during pregnancy improved the pregnancy outcomes. Conclusion: However, practical implementation and referring patients to dentists were less. The gynecologists were aware of the facts but failed to execute at the clinical level. Thus, this bilateral interdisciplinary protocol can thus reduce the incidence of maternal and neonatal complications.